Evaluating implementation effectiveness and sustainability of a maternity waiting homes intervention to improve access to safe delivery in rural Zambia: a mixed-methods protocol - Elizabeth G. Henry; Thandiwe Ngoma; Jeanette L. Kaiser; Rachel M. Fong; Taryn Vian; Davidson H. Hamer; Peter C. Rockers; Godfrey Biemba; Nancy A. Scott (BMC, 2020)
Abstract Background In low-income countries such as Zambia, where maternal mortality rates are persistently high, maternity waiting homes (MWHs) represent one potential strategy to improve access to safe delivery, especially for women living in remote areas. The Maternity Homes Access in Zambia project (MAHMAZ) is evaluating the impact of a MWH model on women's access to safe delivery in rural Zambia. There is a growing need to understand not only the effectiveness of interventions but also the effectiveness of their implementation in order to appropriately interpret outcomes. There is little evidence to guide effective implementation of MWH for both immediate uptake and to promote sustainability in this context. This protocol describes a study that aims to investigate the effectiveness of the implementation of MAHMAZ by not only documenting fidelity but also identifying factors that influence implementation success and affect longer-term sustainability. Methods This study will use mixed methods to evaluate the implementation effectiveness and sustainability of the MAHMAZ intervention. In our study, "implementation effectiveness" means to expand beyond measuring fidelity to the MWH model and includes assessing both the adoption and uptake of the model and identifying those factors that facilitate or inhibit uptake. Sustainability is defined as the routine implementation of an intervention after external support has ended. Quantitative methods include extracting data from existing records at the MWHs and health facilities to analyze patterns of utilization, and conducting a routine health facility assessment to determine facility-level factors that may influence MWH implementation and woman-level outcomes. We will also conduct an experience survey with MWH users and apply a checklist to assess fidelity to the MWH model. Qualitative methods include in-depth interviews and focus group discussions with MWH users, community members and other stakeholders. Qualitative data will be analyzed using an integrated framework drawing constructs from the Consolidated Framework for Implementation Research and the Conceptual Framework for Sustainability. Discussion The findings from this evaluation will be shared with policymakers formulating policy affecting the implementation of MWH and may be used as evidence for programmatic decisions by the government and supporting agencies in deciding to take this model to scale. Trial registration NCT02620436 , Registered 3 December 2015, Prospectively registered (clinicaltrials.gov; for the overarching quasi-experimental impact study).